1991
DOI: 10.1016/0007-1935(91)90044-n
|View full text |Cite
|
Sign up to set email alerts
|

Growth rates and patterns of organs and tissues in the bovine fetus

Abstract: Ninety-two purebred Jersey fetuses from clinically normal dams derived from a variety of sources but unexposed to experimental infection, were killed between 80 and 260 days after conception and dissected to provide basic parameters of a normal population. Organs and tissues were weighed and measured and the equations for the regression of the values on fetal age evaluated. Growth followed a sigmoid curve with rapid changes in growth rate between 140 and 170 days' gestation. While a few variables increased the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
2
1
Order By: Relevance
“…This is the first report of such data in cattle. Richardson et al (1991) reported Jersey fetuses had accelerated kidney growth after 4.7 mo, which is in conflict with our findings. Although the exact reason for this discrepancy is not known, the fact that we observed the same result in 4 different cattle breeds gives credence to our results.…”
Section: Organ Developmentcontrasting
confidence: 99%
“…This is the first report of such data in cattle. Richardson et al (1991) reported Jersey fetuses had accelerated kidney growth after 4.7 mo, which is in conflict with our findings. Although the exact reason for this discrepancy is not known, the fact that we observed the same result in 4 different cattle breeds gives credence to our results.…”
Section: Organ Developmentcontrasting
confidence: 99%
“…The determination or calculation of the age of the fetuses using the three different methods led to somewhat different results, with Habermehl [ 29 ] estimating the age of the fetuses to be the highest and Schnorr and Kressin [ 31 ] the lowest; the age determination according to Richter et al [ 30 ] lay between the two schemes. According to Richardson et al [ 32 ] the vertex–anus length follows an approximately linear function with a slight kink after the 150th day of gestation. Similarly, the three schemes we applied approximately follow a linear progression.…”
Section: Discussionmentioning
confidence: 99%
“…At present, research has not characterized how the rate of parenchyma growth changes over the entire early life developmental phase. However, if mammary parenchyma growth occurs in a sigmoidal pattern (Berg and Butterfield, 1976;Batt, 1980;Richardson et al, 1991;Bollwein et al, 2017) over the course of development from birth to postpuberty, then it is possible that increased nutrient supply can alter the rate of development and composition of gain. As such, ELE heifers might be expected to reach a greater rate of parenchymal growth earlier than RES heifers (Meyer et al, 2006b,c) but of different cellular composition.…”
Section: Discussionmentioning
confidence: 99%